(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The research topic in this study focuses on the "Impact of Information and Communication Technologies (ICT) in Primary Education: Experiences of Teachers in Bogotá, Colombia." This research starts with data collection and analysis along with interviews in the format of semi-structured questions and various sources of information. Our results are evidenced by surveys carried out by 3 Universities in the country that highlight the experiences lived by teachers. Recognizing the strengths of teachers in the face of ICT. Seeking to make the teaching role visible in the face of the adaptation of ICT in the classroom, it is proposed due to the little documentation found on the Teacher-ICT relationship.